Electroplating Line Flexible Control using P-Time Petri Nets Modeling and Hoist Waiting Times Calculation - Chetouane, Fatah (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
In automated electroplating lines, product quality depends on soak times in chemical tanks while line throughput depends on hoist moves cycle time. These parameters are antagonistic since on-line tuning of cycle time interferes with processing duration and thus quality, and vice versa. Furthermore, on-line tuning actions performed without exploiting process flexibility may affect hoist moves schedule feasibility and call for complex scheduling at the on-line level. In this paper a flexible control for electroplating lines (EPL) is proposed that allows quality and throughput tuning within calculated margins and with no need for hoist moves rescheduling. Firstly a P-time Petri Nets (P-time PNs) tool is used to model hoist move sequence. Afterwards, linear programs (LP) are proposed to determine cycle time and soak times tuning margins without the need to reschedule hoist moves. Flexibility will be achieved using empty-hoist wait times.